TAMAN UMUM RAMAH DISABILITAS TINGKAT RT/RW DI KELURAHAN PELAMBUAN KOTA BANJARMASIN - Vita, Hargita Saputri Mei; Dahliani, Dahliani (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
Banjarmasin City, known as the city of a thousand rivers, focuses on increasing green open spaces and clean rivers and creating an inclusive city. Over time, Banjarmasin has developed various facilities that are more accessible, including inclusive markets, easily accessible public health facilities, and paths and ramps in public buildings.The main objective of this design is to develop a disability-friendly park that is in accordance with the needs of people with disabilities, following applicable regulations and standards. This park aims to meet accessibility requirements and provide an inclusive open space for people with disabilities. The method used in this design is behavioral architecture, by considering user habits. The design of this disability park is expected to provide an inclusive experience and ensure maximum accessibility for all visitors. All elements of the park, from pedestrian paths to supporting facilities such as signage and play areas, are designed to meet the needs of people with disabilities and ensure the comfort and safety of visitors.